IMPROVING DETENTION IN FOOTBALL PLAYERS - Eduard Leonard GUȚĂ (Bulletin of the Transilvania University of Braşov: Series IX Sciences of Human Kinetics, 2019)
“In this paper are highlighted the main concepts of training and improvement of detention to football players. Detention is an extremely important ingredient in football, as it is a combination of power, conditioning, flexibility and competence. Such features are essential to the success of a footballer and can be improved by appropriate training. For football players, detention is essential and can be and is commonly used as a measurement tool to assess the strength, explosive power and ability of the footballer to use power. Death to footballers can be enhanced by physical exercises in which muscles exercise maximum force at short intervals to increase dynamic performance. Through these exercises, the muscles are subjected to rapid elongation followed by an immediate shortening. In many situations, football players are attributed to their opponents in the air during some jumping to hit the ball. So, in order to win a duel in the air, the former should be able to make a higher jump. At the same time, a footballer with a longer flight has the ability to keep his body balanced in the air, making head strokes.”